Clinical evaluation of prosthetic medial glenohumeral ligament repair in the dog (ten cases) - Fitch, R. B.; Breshears, L.; Staatz, A.; Kudnig, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
This is a clinical evaluation of ten clinical cases of medial shoulder luxation and instability repaired using prosthetic medial glenohumeral ligament sutures intended to replicate the mechanical function of the medial glenohumeral ligament, thereby restoring normal motion to the scapulohumeral joint without altering regional anatomy. Eight dogs presented with medial shoulder instability, one case with congenital shoulder luxation and one traumatic induced complete shoulder luxation. Evaluations were performed by gait, orthopedic and radiographic examinations as well as owner questionnaire. Nine of ten dogs had good to excellent clinical outcomes. This paper presents a surgical technique that restores normal stability, congruency, mobility and function to the shoulder joint without altering regional anatomy.This case series of ten clinical cases describes a surgical technique for stabilization of medial shoulder luxation and instability intended to replicate the function of the medial glenohumeral ligament, thereby restoring normal motion to the scapulohumeral joint without altering regional anatomy.
Keywords: Shoulder; luxation; scapulohumeral joint; prosthetic ligament